THE EFFECT OF TOURISM DEVELOPMENT ON COMMUNITY PARTICIPATION AND SOCIAL-ECONOMIC CONDITIONS IN THE NATURAL TOURISM AREA OF MALINO, GOWA REGENCY - asdi asdi (Universitas Muhammadiyah Makassar, 2021)
The development of tourism is expected to increase participation and socio-economic conditions of the community around the tourism object. The purpose of this research is to find out how the effect is partial; (1) Development of tourism on community participation, (2) development of tourism on socio-economic conditions, (3) participation on socio-economic conditions of the community, and (4) simultaneous influence of tourism development and community participation on socio-economic conditions of the community around tourism objects. The study was conducted on the natural tourism object of Malino, in Tinggimoncong District, Gowa Regency by selecting a sample of 100 families as respondents. The data collection technique used a questionnaire, while the data processing and analysis used the product-moment correlation technique and the coefficient of determination, as well as the t-test significance test. The results of data analysis showed that partially; tourism development has a significant effect on participation and socio-economic conditions of the community, and simultaneously, tourism development and participation have a significant effect on the socio-economic conditions of the community around tourism objects.